Elemental and isotopic determination of lead (Pb) in particulate matter in the Brazilian city of Goiânia (GO) using ICP-MS technique - Gemeiner, Hendryk [UNESP]; de Araujo Dourado, Thiago [UNESP]; Sulato, Everton Tiago [UNESP]; Galhardi, Juliana Aparecida [UNESP]; Gomes, Ana Carla Fernandes; de Almeida, Eduardo; Menegário, Amauri Antonio [UNESP]; Gastmans, Didier [UNESP]; Kiang, Chang Hung [UNESP] (Springer Nature, 2017)
The toxic metal lead (Pb) can be harmful to human health in various manners, but is also considered as a distinguished tracer of environmental pollution since the relative abundance of its four stable isotopes with the atomic masses of 204, 206, 207, and 208 varies with the emission source. This study is focused on the Pb concentrations and isotope ratios in the particulate matter of the Brazilian city of Goiânia in order to determine the main Pb emission sources. Particulate matter samples were collected on clean Teflon filters during rainy and dry season in 2014 in the center of Goiânia city near main roads with a high traffic volume. Pb concentrations as well as stable Pb isotope ratios of the particulate matter samples were analyzed by inductively coupled plasma-mass spectrometry. To apply this analytical technique successfully, it was necessary to optimize parameters in case of acquisition time, detector dead time, and mass discrimination, which affect the measurement accuracy and precision. Results showed that Pb concentrations in Goiânia were different between rainy and dry season. Pb concentrations showed higher values and less variation in dry season than in rainy season. Pb isotope ratios demonstrated significant variations between dry and rainy season. An enrichment of 206Pb isotopes related to 207Pb and 208Pb isotopes was observed in dry season. However, the comparison of the obtained isotopic Pb signature with data of potential Pb sources from previous studies indicated that traffic-related sources should be considered as main Pb source in the particulate matter of Goiânia. These assumptions were incorporated by the calculation of the contribution factor of Pb coming from traffic-related sources by applying binary mixing equations.
Keywords: Air pollution; ICP-MS; Industrial emissions; Lead isotope ratios; Particulate matter